INVESTIGATION OF DIFFUSE INTERSTELLAR BANDS OF ORGANIC MOLECULES IN THE SPECTRA OF CEPHEID STARS - Kashuba, S. V.; Andrievsky, S. M.; Chekhonadskikh, F. A.; Korotin, S. A.; Kovtyukh, V. V.; Luck, R. E. (Одеські астрономічні публікації, 2016)
We describe an effective method of investigation of the Diffuse Interstellar Bands (DIBs) in the spectra of Cepheid stars. DIBs are believed to originate from the absorption of such carriers as polycyclic aromatic hydrocarbons in the interstellar gaseous clouds located between an observer and the stars whose spectra were recorded. We performed a detailed consideration of the DIB at 6613 A in our sample of spectra for more than 250 stars. The quantitative characteristics of the DIB absorption features will be studied in connection with the interstellar absorption data, and after that, they will be used in the mapping of the Galactic disc.